2014
DOI: 10.3892/mco.2014.481
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between benign and malignant ovarian masses in the preoperative period using neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios

Abstract: Abstract. The aim of this study was to evaluate the association between preoperative neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) and the pathological diagnosis of adnexal masses. The predictive effect of inflammatory markers on epithelial ovarian cancer was also investigated. The present study included a total of 306 patients with adnexal masses who underwent surgical resection and the diagnosis was based on pathological investigation. The patients were divided into six groups b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 22 publications
(26 reference statements)
1
33
1
1
Order By: Relevance
“…Increased NLR is also seen in cancers such as non-smallcell lung cancer, 41 colon, 42 triple-negative breast, 43 prostate, 44 gastric, 45 hepatocellular, 46 pancreas, 47 and epithelial ovarian, 48 and other cancers. Although not a sine qua non, elevated NLR can now be recognized as a general hallmark of cancer.…”
Section: G(m)-csf Is Responsible For Elevated Neutrophil-to-lymphocytmentioning
confidence: 99%
“…Increased NLR is also seen in cancers such as non-smallcell lung cancer, 41 colon, 42 triple-negative breast, 43 prostate, 44 gastric, 45 hepatocellular, 46 pancreas, 47 and epithelial ovarian, 48 and other cancers. Although not a sine qua non, elevated NLR can now be recognized as a general hallmark of cancer.…”
Section: G(m)-csf Is Responsible For Elevated Neutrophil-to-lymphocytmentioning
confidence: 99%
“…Six studies comprising 1054 patients reported the PLR in patients with malignant ovarian masses and the controls [20][21][22][23][24][25] .…”
Section: Numerical Differences In Plr Between Patients With Malignantmentioning
confidence: 99%
“…The NOS scores, which indicated the quality of these studies, ranged from 6 to 8. Five of the selected eligible studies presented data regarding the association between the PLR and OS [14][15][16][17][18] , five studies discussed the link between PLR and PFS [15][16][17][18][19] , and six examined numerical differences in PLR between patients with malignant ovarian masses and the controls [20][21][22][23][24][25] . The disease characteristics in 12 studies are summarized in Table 2.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…It was found that neutrophils increased and lymphocytes relatively decreased as a result of the systemic inflammatory response [8]. Numerous studies have demonstrated the association between NLR and PLR with the ovarian cancers [46, 8]. In the current study, the association between NLR and PLR with BOTs has been investigated.…”
Section: Discussionmentioning
confidence: 83%